A boy with partial trisomy of chromosome 3q24–q28 from paternal balanced insertion and multiple congenital anomalies1. Issue 2 (15th January 2013) - Zhu, Haiyan; Hu, Yali; Zhu, Ruifang; Yang, Ying; Zhu, Xiangyu; Wang, Wanjun
Abstract Although many patients with duplication 3q syndrome have been described reports on duplication derivatives from an insertion are rare in the previous literature. Here we describe the genotype and phenotype of a 32‐month‐old boy with a partial trisomy of 3q24–q28. We carefully mapped the aberration with SNP‐array analysis, and found a duplication region of 44 Mb. By conventional cytogenetic techniques including fluorescence in situ hybridization (FISH) and spectral karyotyping (SKY) analysis, the patient was found to have inherited a derivative chromosome 6 from his father, which was contained a direct insertion from 3q24–28. The main clinical features of the patient included severe mental retardation, postnatal developmental delay, ventricular septal defect (VSD), and craniofacial anomalies including cleft palate, frontal bossing, hypertelorism, and a broad nasal bridge. The symptoms partially overlap with previously reported patients with duplication in the same region. Prenatal diagnosis for the fetus of this family was performed based on the results of genetic tests and ultrasonic evaluation. © 2013 Wiley Periodicals, Inc.